Study of storage devices properties for steganographic data hiding in cluster file systems - Shekhanin, K.Yu.; Gorbenko, Yu.I.; Gorbachova, L.O.; Kuznetsov, A.A. (Radiotekhnika, 2020)
Methods for technical steganography have been developed in recent years. Hiding of information in such systems is achieved by using properties artificially created by human while constructing various technical means. An example of technical steganography is the application of the features of constructing clustered file systems. This makes it possible to hide information effectively by changing the alternation of individual clusters, the so-called сover files. The names of such files are the key information and it is extremely difficult to recover a hidden message without links (i.e. without names) of cover files. This work describes and analyzes various modern information storage technologies, namely HDD, Flash-USB, SSD. We have analyzed different indicators such as the number of implemented products, price, speed of reading and writing. The important indicators of storage media efficiency with regard to steganographic methods of hiding information in cluster file systems were also analyzed. For example, we have investigated the speed of sequential reading / writing and the speed of access to a random cluster that is similar to the speed of access to a fragmented file. For this, we used the test results from the UserBenchmark resource. Tests were performed using Sequential and Random4k methods. In conclusion, an assessment of information carriers is given and recommendations are given on using the method of hiding data by mixing clusters in the structure of the file system.